Incidence of esophageal injury after pulmonary vein isolation in patients with a low body mass index and esophageal temperature monitoring at a 39 °C setting. Issue 1 (19th June 2014) - Kiuchi, Kunihiko; Okajima, Katsunori; Shimane, Akira; Kanda, Gaku; Yokoi, Kiminobu; Teranishi, Jin; Aoki, Kousuke; Chimura, Misato; Tsubata, Hideo; Miyata, Taishi; Matsuoka, Yuuki; Toba, Takayoshi; et al.
Abstract: Background: Esophageal injury following catheter ablation of atrial fibrillation (AF) is reported to occur in 35% of patients. Even with a low energy setting (20–25 W), lesions develop in 10% of patients. Body mass index (BMI) has been reported to be a predictor of esophageal injury, indicating that patients with a low BMI (<24.9 kg/m 2 ) are at a higher risk. We hypothesized that catheter ablation with a lower energy setting of 20 W controlled by esophageal temperature monitoring (ETM) at 39 °C could prevent esophageal injury even in patients with a BMI <24.9 kg/m 2 . Methods: Twenty patients with AF were included (age, 63±8 years; BMI, 22.9±1.3 kg/m 2, left atrium diameter, 44±11 mm). If the esophageal temperature probe registered a temperature of >39 °C, radiofrequency (RF) application was stopped immediately. RF application could be performed in a "point by point" manner for a maximum of 20 s. Endoscopy was performed 1–5 days after ablation. Results: Esophageal mucosal injury was not observed in any patient in the study. Conclusions: Catheter ablation using ETM reduced the incidence of esophageal injuries, even in patients with a low BMI.